Smart grass cutter/ Muhammad Hifzhan Ruslan, Muhammad Ammar Maznan and Yusri Aizat Mohd Yasir Afkam - Ruslan, Muhammad Hifzhan; Maznan, Muhammad Ammar Irfan; Mohd Yasir Afkam, Yusri Aizat (2018)
This project is about a grass cutter machine that using arduino and bluetooth to control. The aim of this project is to decrease the workload of worker and to reduce the time required to cut the grass in certain area. A prototype can be connected and controlled by the phone via bluetooth module. Bluetooth module is a device that receive the signal from the control device and synchronous the waveform from the controller and send it to the prototype. In this project, the bluetooth module is connected to the arduino and the arduino will be put some coding. The blade motor was placed on the bottom of the prototype. The Arduino consist of both a physical programmable circuit board and a piece of software or IDE that runs in the computer which is used to write and upload computer code to the physical board. The output is the LED and motor.